2020
DOI: 10.1111/jcmm.14930
|View full text |Cite
|
Sign up to set email alerts
|

LPS‐induced inflammation desensitizes hepatocytes to Fas‐induced apoptosis through Stat3 activation—The effect can be reversed by ruxolitinib

Abstract: Recent studies have established a concept of tumour necrosis factor‐α (TNF‐α)/Fas signalling crosstalk, highlighting TNF‐α as a critical cytokine in sensitizing hepatocytes to death induced by Fas activation. However, in the exact inflammatory response, besides TNF‐α, many other mediators, that might modulate apoptotic response differentially, are released. To resolve the issue, we studied the effects of lipopolysaccharide (LPS), one of the crucial inductors of inflammation in the liver, on apoptotic outcome. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…Various in vitro and in vivo studies have suggested complex crosstalk between their signaling pathways. Furthermore, it was found that TNF-α and FasL affected each other’s activity and expression ( 8 , 24 ). Therefore, we hypothesized that the rs763110 genotype might be associated with TNF-α concentration in plasma, which had not been previously investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various in vitro and in vivo studies have suggested complex crosstalk between their signaling pathways. Furthermore, it was found that TNF-α and FasL affected each other’s activity and expression ( 8 , 24 ). Therefore, we hypothesized that the rs763110 genotype might be associated with TNF-α concentration in plasma, which had not been previously investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA was extracted from peripheral blood mononuclear cells using TRIzol (Invitrogen by Life Technologies [LT], Grand Island, NY, USA), converted to complementary DNA and amplified in duplicates by qPCR in an ABI Prism 7500 Sequence Detection System (Applied Biosystems by LT). Gene expression of TNF-α and glyceraldehyde 3-phosphate dehydrogenase was assessed using TaqMan Assays (Applied Biosystems by LT) and presented as RNA relative quantity, as previously described ( 8 ).…”
Section: Methodsmentioning
confidence: 99%
“…Rux (C10891361, Shanghai Chemical Industry Park, Shanghai, China) was dissolved in 30% polyethylene glycol 300 (PEG300) and 3% dimethyl sulfoxide (DMSO) as previously described (26) and diluted with distilled water (dH2O) to the required concentrations. In the first experiment, mice were treated 30 minutes after MCAO with 4 different doses of Rux (30, 60, 90, and 120 mg/kg) by oral gavage twice daily for three days.…”
Section: Drug Administrationmentioning
confidence: 99%
“…LPS induced inflammation by activating HIF1 and hypoxia pathway gene responses in the testis, 58,59 as well as apoptosis by both intrinsic and extrinsic pathways. [60][61][62] In our acute hearing loss model, LPS may induce oxidative stress, provoke inner ear cells to release inflammatory cytokines, and eventually reduce Hdac2 activity or level. 54 In the present study, we use the LPS animal model to further explore the specific mechanisms of Hdac2 in cochlear hair cell apoptosis.…”
Section: Discussionmentioning
confidence: 94%